Some Commutative Neutrix Convolutions Involving the Fresnel Integrals - Fisher, Brian; Nonlaopon, Kamsing; Sritanratana, Gumpon (Sarajevo Journal of Mathematics, 2024)
The Fresnel cosine integral C$(x)$, the Fresnel sine integral S$(x)$ and the associated functions $C_+(x)$, $C_-(x)$, $S_+(x)$ and $S_-(x)$ are defined as locally summable functions on the real line. Some convolutions and commutative neutrix convolutions of the Fresnel sine integral and its associated functions with $x^r$ are evaluated. 1991 Mathematics Subject Classification. 33B10, 46F10